Four-dimensional nilpotent diassociative algebras - Basri, Witriany; Sattarovich, Rakhimov Isamiddin; Rikhsiboev, Ikrom M. (Hilaris SRL, 2015)
The paper is devoted to structural properties of diassociative algebras. We introduce the notions of nilpotency, solvability of the diassociative algebras and study their properties. The list of all possible nilpotent diassociative algebra structures on four-dimensional complex vector spaces is given.